E-Cigarette Awareness, Usage Patterns, and Sociodemographic Determinants among Malaysians Adolescents: A Cross-Sectional Study - Kamal, Izdihar; Mohd Abd Wahab, Nabilah; Mawaddah Mohammad, Nurul; Ahmad, Rashidi; Khalis Abdul Karim, Muhammad; Mohd Diah, Hatikahaty; Ahmad Dahari, Munirah; Biha Mohamed Nafis, Nur; Abdullah Sani, Mohd Faris; Kabeer, Sulayman Muhammad; Mohamed Nafis, Nur Biha; Mohd Radzi, Juliana (Makara Journal of Health Research, 2026)
Background: Electronic cigarette (e-cigarette) use among Malaysian adolescents is rising rapidly, raising significant public health concerns. This study assessed awareness, understanding of risk, and e-cigarette use among secondary school students in Negeri Sembilan, Malaysia, and identified sociodemographic predictors of use. Methods: A cross-sectional survey was conducted among 323 students from three government secondary schools using a validated questionnaire. Data were then analyzed using descriptive statistics and logistic regression. Results: Nearly one-third (31.9%, N = 103) reported prior e-cigarette use. Although 63.2% (N = 204) demonstrated good awareness, only 14.6% (N = 47) understood associated health risks. Peers (32.5%, N = 105) and the internet (29.1%, N = 94) were the primary sources of information, while school-based interventions remained largely passive. Male gender (Adjusted Odds Ratio [AOR] = 7.63, p < 0.001), age 16 (AOR = 4.56, p = 0.002), and having a family member who smoked or vaped (AOR = 3.97, p < 0.001) were significant predictors of use. Conclusion: Despite good awareness, understanding of risk remained critically low, revealing a gap that current school-based efforts have failed to address. In particular, male, older age, and family smoking exposure were key predictors of use. Overall, targeted health education and stronger regulatory measures are urgently needed to reduce adolescent vaping in Malaysia.